Pemanfaatan Teknologi dalam Model Pembelajaran Olah Alur pada Pembelajaran Menulis Cerpen - Anisa Ulfah; Elena Jesica; Lailatul Fitriyah; Ghaitsa Shofa Putri Amalia; Mita Yulianingtyas; Putri Dewi Amelya (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
The use of technology in learning is something that educators need to continue to innovate so that the learning process is in line with current developments. The use of this technology can be developed in selecting learning models because it is a learning component used to support the achievement of learning success. The Olah Alur learning model is a learning model developed by optimizing the use of technology and using modeling methods to emphasize short story literacy activities as a reference in producing a new short story according to the characteristics and needs of students. The purpose of this research is to explain the use of technology used in the Flow Process learning model. The method used in this research is descriptive qualitative method. Based on the results of data analysis, it was found that there were five uses of technology in the Olah Alur learning model, including the use of website spinner, Google Drive, PowerPoint, digital LKPD, and social media. These media are used as an effort to improve the quality of learning to write short stories at Al-Mubtadiin Babat Lamongan Integrated Middle School. Thus, it can be concluded that the use of technology is used as a medium and learning resource for students to be able to provide quality experiences.